2023
DOI: 10.7762/cnr.2023.12.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Protein Intake From Different Animal and Plant Origins and the Risk of Non-Alcoholic Fatty Liver Disease: A Case-Control Study

Abstract: Previous studies have frequently reviewed how different macronutrients affect liver health. Still, no study centered around protein intake and the non-alcoholic fatty liver disease (NAFLD) risk relationship. This study aimed to examine the association between the consumption of total and different sources of protein and NAFLD risk. We allocated 243 eligible subjects to the case and control groups, including 121 incidence cases of NAFLD, and 122 healthy controls. Two groups were matched in age, body mass index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“… Association of nut intake with NAFLD according to a random effects meta-analysis. CI, confidence interval [ 2 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 33 , 34 , 35 , 36 ]. Black dots: odds ratio value.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… Association of nut intake with NAFLD according to a random effects meta-analysis. CI, confidence interval [ 2 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 33 , 34 , 35 , 36 ]. Black dots: odds ratio value.…”
Section: Figurementioning
confidence: 99%
“… NOS, Newcastle-Ottawa Scale; BMI, body mass index; PAL, physical activity level; SSB, sugar-sweetened beverages; MUFA, monounsaturated fatty acids; PUFA, polyunsaturated fatty acids; DHA, docosahexaenoic acid; EPA, eicosapentaenoic acid; HEI-2015, Healthy Eating Index 2015; CVD, cardiovascular disease; HbA1c, Hemoglobin A1c. [ 2 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 33 , 34 , 35 , 36 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Such fatty foods might again increase carnitine depletion due to overconsumption.Therefore 'Mediterranean Diet' based on lean meat, lamb, fish, low-fat milk, nuts & fruits, is found to be effective. A case-control study by Khazaei et al, 2023, found a significant reduction in liver enzymes of the case group NAFLD subjects, after consuming a Green Mediterranean diet, more plant proteins (soy, nuts, vegetables and grains) and less animal protein.…”
Section: Therapeutic Effects Of Carnitine: Supplementation In the For...mentioning
confidence: 99%
“…For instance, foods of animal origin are a source of animal protein and saturated fatty acids which may increase insulin resistance and CVD risk while foods of plant origin are a source of plant proteins, fibre and bioactive compounds, which are associated with cardiometabolic benefits ( 22 , 23 ) . Data from population-based studies suggest a high consumption of animal protein (especially red and/or processed meat) may increase the risk of NAFLD ( 24 , 25 ) , while greater intake of plant proteins and fish may be protective ( 26 , 27 ) . A diet that emphasises plant sources of protein is also in line with the Mediterranean diet composition that is recommended in NAFLD clinical guidelines ( 4 ) .…”
mentioning
confidence: 99%